A mixed methods evaluation of the impact of ECHO® telementoring model for capacity building of community health workers in India - Rajmohan Panda; Supriya Lahoti; Nivedita Mishra; Rajath R. Prabhu; Kalpana Singh; Apoorva Karan Rai; Kumud Rai (BMC, 2024)
Abstract Introduction India has the largest cohort of community health workers with one million Accredited Social Health Activists (ASHAs). ASHAs play vital role in providing health education and promoting accessible health care services in the community. Despite their potential to improve the health status of people, they remain largely underutilized because of their limited knowledge and skills. Considering this gap, Extension for Community Healthcare Outcomes (ECHO)® India, in collaboration with the National Health System Resource Centre (NHSRC), implemented a 15-h (over 6 months) refresher training for ASHAs using a telementoring interface. The present study intends to assess the impact of the training program for improving the knowledge and skills of ASHA workers. Methods We conducted a pre-post quasi-experimental study using a convergent parallel mixed-method approach. The quantitative survey (n = 490) assessed learning competence, performance, and satisfaction of the ASHAs. In addition to the above, in-depth interviews with ASHAs (n = 12) and key informant interviews with other stakeholders (n = 9) examined the experience and practical applications of the training. Inferences from the quantitative and qualitative approaches were integrated during the reporting stage and presented using an adapted Moore's Expanded Outcomes Framework. Results There was a statistically significant improvement in learning (p = 0.038) and competence (p = 0.01) after attending the training. Participants were satisfied with the opportunity provided by the teleECHO™ sessions to upgrade their knowledge. However, internet connectivity, duration and number of participants in the sessions were identified as areas that needed improvement for future training programs. An improvement in confidence to communicate more effectively with the community was reported. Positive changes in the attitudes of ASHAs towards patient and community members were also reported after attending the training. The peer-to-peer learning through case-based discussion approach helped ensure that the training was relevant to the needs and work of the ASHAs. Conclusions The ECHO Model ™ was found effective in improving and updating the knowledge and skills of ASHAs across different geographies in India. Efforts directed towards knowledge upgradation of ASHAs are crucial for strengthening the health system at the community level. The findings of this study can be used to guide future training programs. Trial registration The study has been registered at the Clinical Trials Registry, India (CTRI/2021/10/037189) dated 08/10/2021.